A Report from the Higher Education Review Board (HERB): Assessment of Undergraduate Student Learning Outcomes in Food Science. Issue 2 (April 2016) - Hartel, R.W.; Iwaoka, W.T.
Abstract: For the past 15 years, Institute of Food Technologists (IFT) has mandated assessment of undergraduate student learning outcomes as the basis for approving food science (FS) programs. No longer is a check‐off course system sufficient to be an IFT‐approved program. The 4 steps to gaining IFT approval include developing learning outcomes for all required FS courses, developing outcomes for the program as a whole, assessing student learning through a comprehensive series of assessment tools, and developing and reporting a plan to use the assessment data collected for continuous program improvement. This article reviews these steps in some detail, providing guidance on possible approaches that may be used. In the end, the aim of the IFT requirements is to improve student learning in FS to advance the field.